Evaluasi Terhadap Penerimaan SIMLITABMAS Universitas Riau Menggunakan Model TAM - Sukamto Sukamto; Gita Sastria; Resti Pujasartika (InfoTekJar : Jurnal Nasional Informatika dan Teknologi Jaringan, 2019)
This research aims to describe the acceptance of SIMLITABMAS (Information System of Research and Community Service) with several variables, such as Usefulness, Ease of Use and Acceptance of SIMLITABMAS. Data were collected through questionnaire using Likert scale to 101 SIMLITABMAS’s users. Data analysis is done by validity and reliability test. In classic assumption test, normality, multicolinearity and heterokedastisitas. moreover the result test there are multiple correlation test,  coefficient of determination (R2) and f test. The result of this research shows that there are a correlation between the Usefulness and Ease of Acceptance with a strong closeness (0,558). Futhermore Usefulness and Ease have a significant effect on the acceptance of SIMLITABMAS amounted to 31.1%.